ANALISIS NORMATIF TERHADAP PENGAJUAN GUGATAN PERWAKILAN KELOMPOK (CLASS ACTION) DI PENGADILAN MENURUT HUKUM ACARA PERDATA - ENDANG MUSTIKOWATI (Jurnal Yustisiabel, 2019)
This research aims to study the object of research from the aspect of legal statutory arrangements regarding the position of the Lawsuit (Class Action) in the law of civil liability. The research method used was the normative legal research i.e. research on legal materials which adhere to the provisions of the applicable legislation. The conclusion that the terms of Formyl which is a condition sine qua non filed Class Action outlined PERMA number. 1 year 2002 is there a group (class) that is a member of the group consists of many individual (individuals) who have in common the fact and the legal basis of the filing procedures in class action lawsuit. The filing of the lawsuit class action in so far as this is not regulated in law but regulated in the rules of the Supreme Court (PERMA) Number 1 of the year 2002 Concerning the procedures for the community Representative Plaintiff Filings (Class Action). As for the procedure for the settlement of a Class Action lawsuit is: a. petition for filing the lawsuit Class Action basis b. certification process or the granting of the permit Notification c. d. examination and proof in Class Action e. implementation of the verdict.